A comparison between temperature dependent and constant Young's modulus values in investigating the effect of the process parameters on thermal behaviour during friction stir welding: Vergleich zwischen den temperaturabhÃ¤ngigen und konstanten ElastizitÃ¤tsmodulwerten in der Untersuchung der Prozessparameter auf die WÃ¤rmewirkung beim RÃ¼hrreibschweiÃen - Meyghani, B. (Wiley-VCH Verlag, 2018)
One of the most intriguing joining techniques in aerospace and automotive industries is friction stir welding. In this welding, temperature has an important effect on the quality and the integrity of the weld. Welding parameters, on the other hand, highly affect the temperature. Many authors used finite element methods to study the effect of the process parameters on thermal behavior by using constant Young's modulus, while, it should decrease as the temperature increases. Therefore, the proper definition of the Young's modulus during the study of the effect of the process parameters on thermal behavior, will increase the accuracy of the model. In this paper, to properly investigate thermal behavior, temperature dependent and constant Young's modulus values are applied in different models to examine the accuracy of those models. In addition, the influence of the process parameters on thermal behavior is studied. More accurate results are obtained from the model in which temperature dependent values of the Young's modulus is used. The effect of the welding parameters and different Young's modulus values on the size, shape and temperature of the welding string zone is studied and reported in detail. Â© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim